ENDOGENOUS DIGOXIN-LIKE IMMUNOREACTIVE SUBSTANCE (S) (EDLIS) AND RENIN-ALDOSTERON IN VOLUME REGULATION OF PATIENTS WITH EARLY CIRRHOSIS - Hakan BOZKAYA; Özden UZUNALİMOĞLU; Ali ÖZDEN; Cihan YURTAYDIN (Turkish Journal of Gastroenterology, 2020)
-